2002
DOI: 10.1002/bdd.338
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the gastric pH profiles of unfed and fed cynomolgus monkeys as pharmaceutical product development subjects

Abstract: Gastric pH is an important factor which significantly affects the dissolution of drugs, and therefore their bioavailability. In this study, the gastric pHs were measured directly with a miniature pH electrode inserted through the nostril into the body of the stomach of cynomolgus monkeys. Results from three separate sets of measurements using the same male monkeys indicated that the median gastric pH profiles of unfed monkeys were low, fluctuating between pH 1 and pH 3. However, the median gastric pHs in fed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 11 publications
0
23
3
Order By: Relevance
“…A recent study has revealed that the gastric pH of unfed cynomolgus monkeys is generally low and that at least 60% of the animals show less than pH 5 during a 24 h measurement period with the median pH between 1 and 3. 25) There was only a small difference in the ratio of animals showing low gastric pH compared to our background data. Although the exact dose which showed a significant effect was not clarified, the inhibitory effect of CS-526 against gastric acid secretion in cynomolgus monkeys was obvious after oral or intravenous administration.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…A recent study has revealed that the gastric pH of unfed cynomolgus monkeys is generally low and that at least 60% of the animals show less than pH 5 during a 24 h measurement period with the median pH between 1 and 3. 25) There was only a small difference in the ratio of animals showing low gastric pH compared to our background data. Although the exact dose which showed a significant effect was not clarified, the inhibitory effect of CS-526 against gastric acid secretion in cynomolgus monkeys was obvious after oral or intravenous administration.…”
Section: Discussioncontrasting
confidence: 51%
“…Although the data from non-human primates would be useful for the prediction of clinical study results due to their phylogenetic similarities, the background knowledge of gastric acid secretion in primates is still lacking. There are only a few reports regarding the physiologic state of gastric acid secretion [22][23][24][25][26][27] and less than 10 reports of pharmacodynamic studies. [28][29][30][31][32][33][34] In these pharmacodynamic studies, gastric juice or infused wash solution was collected from acute gastric fistulae in anesthetized animals or nasogastric tubes in monkey chair restrained animals, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of pentagastrin important for improving overall predictability of the model (35) of this species for food effect studies. Kondo et al showed the gastric pH after feeding of a standard biscuit-type meal to be higher in cynomolgus monkeys than the fed state pH in humans (26). Thus, optimization of the fed state test meal may be required before the monkey could yield food effect data similar to the human.…”
Section: In Vivo Methodsmentioning
confidence: 99%
“…In our previous study, the gastric pHs of cynomolgus monkeys after they ate 108 g of biscuit-type solid food shifted to a neutral range of pH 5-7, and remained in this pH range for about 9 h [22]. It has been reported that the gastric pH of healthy young humans temporarily shifts from an acid range to a more neutral range of pH 5-6 after having a standard meal, but it returns to the basal acid pH range within a brief period [29][30][31].…”
Section: Oro-caecal Transit Time Of Liquids In Fed Cynomolgus Monkeysmentioning
confidence: 97%